Study on the correlation between the dominant microflora and the main flavor substances in the fermentation process of cigar tobacco leaves - Wu, Xue; Hu, Yanqi; Wang, Qian; Liu, Jian; Fang, Song; Huang, Dewen; Pang, Xueli; Cao, Jianmin; Gao, Yumeng; Ning, Yang (Frontiers in Microbiology, 2023)
The flavor of cigar tobacco leaf determines the quality of finished cigar tobacco, and the enhancement of flavor generally relies on microbial fermentation. In this paper, the correlation between the dominant microorganisms and the main flavor substances of cigar tobacco leaves during fermentation and the correlation between the two were investigated to reveal the correlation between microorganisms and flavor and the metabolic pathways of microorganisms affecting the flavor substances. During the fermentation process, the main flavors of cigar tobacco leaves were sweet, light and grassy, with hexanal, 2,6-dimethylpyridine, nonanal, phenylacetaldehyde, naphthalene, and methyl benzoate as the main constituents, and the key microorganisms Haloferax mediterranei, Haloterrigena limicola, Candidatus Thorarchaeota archaeon SMTZ-45, the genera Methyloversatilis, Sphingomonas, Thauera, Pseudomonas, Penicillium, and Aspergillus. Correlation analysis revealed that fungi were negatively correlated with the main aroma and inhibited the main flavor substances, while bacteria were positively correlated with Benzoic acid, methyl ester in the main flavor substances, which was conducive to the accumulation of green aroma. Functional analysis revealed that the dominant bacterial population was producing aroma by metabolizing glycoside hydrolases and glycosyltransferases, performing amino acid metabolism, carbohydrate metabolism and film transport metabolism. The present study showed that the bacterial and fungal dominant microorganisms during the fermentation of cigar tobacco were influencing the production and degradation of the main flavor substances through the enzyme metabolism by the occurrence of the Merad reaction.